Pengaruh Profesionalisme dan Disiplin Melalui Motivasi Kerja terhadap Kinerja Guru Aparatur Sipil Negara pada Madrasah Tsanawiyah Negeri Kabupaten Muaro Jambi - Julihartiny Julihartiny; Arna Suryani; Fakhrul Rozi Yamali; Fakhrul Rozi Yamali (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to describe the professionalism, work discipline, work motivation and performance of ASN teachers at State MTS Muaro Jambi Regency and to analyze the effect of professionalism and work discipline partially and simultaneously directly and indirectly on teacher work motivation and performance, as well as to analyze work motivation on teacher performance. To answer the research objectives, this research is supported by theoretical studies related to the research variables namely professionalism, work discipline, work motivation, and performance. In addition, the authors also look for relevant previous research in the form of previous articles/journals and theses to support this research. The population in this study is ASN MTS teachers in the state of Muaro Jambi, totaling 112 teachers with employee conditions in 2022. Data analysis techniques used in the study This is through path analysis followed by hypothesis testing through the F test (Simultaneous) and the t test (Partial). From the path analysis tests carried out, the result is that professionalism and work discipline have an influence on teacher work motivation and performance, both directly and indirect. This explains that if the organization has good professionalism teachers and the better the work discipline of the teachers, this will further increase employee motivation towards the organization and provide maximum work results. This study concludes professionalism, work discipline, work motivation and employee performance in conditions the good one. In addition, professionalism and work discipline partially and simultaneously have a positive and significant influence on the work motivation and performance of teachers at the State MTS of Muaro Jambi Regency. Likewise, work motivation has a positive and significant influence on teacher performance.